RANCANGAN UNDANG-UNDANG HUKUM ACARA PIDANA DARI PERSPEKTIF POLRI SEBAGAI PENYIDIK - R.M. Pangabean (Masalah-Masalah Hukum, 2010)
The puspose of this paper is to know the progress of political law of legal polity of formulation of Indonesia Criminal Law Procedural Code (RUU HAP), which reviewed from Polri's perspective as investigator, for there is certain view from criminal-law practitioners that Act Number 8 Year 1981 regarding Criminal Law Procedural Code (KUHAP) is inapplicable toward recent condition, whereas most substantial part are still relevant to be applied. The discussion including the progress of implementation of KUHAP for 27 years and any weakness lies within it. The conclusion is, Polri does not allergic to amend KUHAP, but is is a urge to see the concept of the amandment, whether it will be applicable or not, because Republic of Indonesia consists of thousand of secluded Islands, and remote from capical city, for it takes some time to impose limited strict action base on Human rights, while to impose such thing also takes some time to request permition from the judge, whose place far form the official Commissioner Judge.Kata Kunci : RUU Hukum Acara Pidana, Penyidikan.